Dispersed Bone Spicules as a Cause of Postoperative Headache after Retrosigmoid Vestibular Schwannoma Surgery: A Myth? - Ren, Yin; McDonald, Marin A.; Manning, Paul; MacDonald, Bridget V.; Schwartz, Marc S.; Friedman, Rick A.; Harris, Jeffrey P. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives Dispersion of bone dust in the posterior fossa during retrosigmoid craniectomy for vestibular schwannoma (VS) resection could be a source of meningeal irritation and lead to development of persistent postoperative headaches (POH). We aim to determine risk factors, including whether the presence of bone spicules that influence POH after retrosigmoid VS resection.Design Present study is a retrospective case series.Setting The study was conducted at a tertiary skull-base referral center.Participants Adult patients undergoing VS resection via a retrosigmoid approach between November 2017 and February 2020 were included for this study.Main Outcome Measures Development of POH lasting ≥ 3 months is the primary outcome of this study.Results Of 64 patients undergoing surgery, 49 had complete data (mean age, 49 years; 53% female). Mean follow-up time was 2.4 years. At latest follow up, 16 (33%) had no headaches, 14 (29%) experienced headaches lasting <3 months, 19 (39%) reported POH lasting ≥3 months. Twenty-seven (55%) patients had posterior fossa bone spicules detectable on postoperative computed tomography (CT). Age, gender, body mass index, length of stay, tumor diameter, size of craniectomy, the presence of bone spicules, or the amount of posterior petrous temporal bone removed from drilling did not differ significantly between patients with POH and those without. On multivariate logistic regression, patients with POH were less likely to have preoperative brainstem compression by the tumor (odds ratio [OR] = 0.21, p = 0.028) and more likely to have higher opioid requirements during hospitalization (OR = 1.023, p = 0.045).Conclusion The presence of bone spicules in the posterior fossa on postoperative CT did not contribute to headaches following retrosigmoid craniectomy approach for VS resection.
Keywords: bone spicule; retrosigmoid; suboccipital; acoustic neuroma; vestibular schwannoma; headache